PROGRAM VAKSINASI PADA KUCING DI KLINIK HEWAN JOGJA (KHJ - , ROCKY NORRIS B.MANAO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Vaccination is an act or effort made to provide immunity to certain spreadable diseases by injecting the weakened germs into the body of animals. The vaccine injection process first done by weighing cats, health check and vaccinations. The cats requirement to be vaccinated is health and old enough because it affects the success of vaccination. The material for this observation entitled Vaccination Program to Cats at Klinik Hewan Jogja (KHJ) is taken first by interviewing the veterinarian, direct practice and took documentation. The goal is to know the implementation of cats vaccination program at Klinik Hewan Jogja. Implementation of cats vaccination programs at KHJ is good and the level of vaccinated patients increasing every month, of course this is to make healthier life cats.